2016
DOI: 10.1002/lt.24666
|View full text |Cite
|
Sign up to set email alerts
|

Successful donation after cardiac death liver transplants with prolonged warm ischemia time using normothermic regional perfusion

Abstract: The role of donation after cardiac death (DCD) in expanding the donor pool is mainly limited by the incidence of primary nonfunction (PNF) and ischemia-related complications. Even greater concern exists toward uncontrolled DCD, which represents the largest potential pool of DCD donors. We recently started the first Italian series of DCD liver transplantation, using normothermic regional perfusion (NRP) in 6 uncontrolled donors and in 1 controlled case to deal with the legally required no-touch period of 20 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 19 publications
(52 reference statements)
0
43
0
Order By: Relevance
“…Mounting clinical evidence suggests that NRP has a significant positive impact on biliary preservation in the setting of DCD liver transplantation because it limits the length of warm ischemia, restores cellular energy stores, and reconditions the graft prior to cold perfusion and storage . There are now several single‐center series that describe excellent posttransplantation survival rates and virtually no ITBL using DCD livers recovered with postmortem NRP . At our own center, postmortem NRP has been used to recover livers from cDCD donors .…”
Section: Discussionmentioning
confidence: 99%
“…Mounting clinical evidence suggests that NRP has a significant positive impact on biliary preservation in the setting of DCD liver transplantation because it limits the length of warm ischemia, restores cellular energy stores, and reconditions the graft prior to cold perfusion and storage . There are now several single‐center series that describe excellent posttransplantation survival rates and virtually no ITBL using DCD livers recovered with postmortem NRP . At our own center, postmortem NRP has been used to recover livers from cDCD donors .…”
Section: Discussionmentioning
confidence: 99%
“…This should result in less time‐pressure on the retrieval team, easier in situ evaluation of graft quality and expansion of the donor pool with overall improved graft quality . While NRP is a technically feasible approach, it has raised numerous ethical and logistical questions concerning premortem interventions such as administration of heparin, cannulation and including the possibility of resuscitating the donor following declaration of death . These concerns have been partially eliminated by technical innovations (heparin‐coated circuits, initial bypassing the oxygenator to prevent clotting; aortic occlusion balloon to exclude the brain from the perfusion); however, several issues, which have been summarized elsewhere, remain to be elucidated …”
Section: Machine Perfusion–basic Principles and Mechanismsmentioning
confidence: 99%
“…102 Most of the teams are currently using the available ECMO devices modified for NRP, but specifically designed devices dedicated to NRP are also available, providing normothermic, regional, pulsatile and oxygenated perfusion during balloon to exclude the brain from the perfusion); however, several issues, which have been summarized elsewhere, remain to be elucidated. 102,[104][105][106][107]109 There are also certain differences in the use of NRP in uncontrolled and controlled DCD donors. 102 In uncontrolled DCD (Maastricht category II-unsuccessful resuscitation), cardiac arrest is unexpected, and death is typically declared before the possibility to consent for organ donation.…”
Section: Further Applicationsmentioning
confidence: 99%
“…They found HOPE treatment of DCD livers significantly decreased graft injury regarding peak of alanine-aminotransferase (ALT), intrahepatic cholangiopathy, biliary complications, and improved 1-year graft survival, achieving similar results as control DBD livers in all investigated endpoints. De Carlis et al reported a series of 7 HCC patients transplanted with DCDs with extended period of WIT (>20 minutes) where they applied HMP after normothermic regional perfusion achieving 100% graft and patient survival with no incidence of ischemic cholangiopathy (77).…”
Section: Transplant For Hcc With Mp Technologymentioning
confidence: 99%